Determinants of non-cash payments in Asian countries - Ruixin Chen (2020)
© 2019 IOP Publishing Ltd. All rights reserved. Non-cash payments, such as payment cards and digital payment, are more efficient ways to complete transactions when compared to cash payment. This study investigates the factors that influence the use of non-cash payments in 10 Asian countries, namely China, India, Indonesia, Japan, Malaysia, Philippines, Singapore, South Korea, Thailand, and Vietnam. A panel data is used in this study and the period 2016-2017 is considered. To address the ill-posed problem caused by limited observations, generalized maximum entropy (GME) estimator is employed. The purposes of the study are to identify the cross-country determinants of non-cash payments and prove that GME estimator is the most effective estimation method. The results of data show that online banking penetration and debit card penetration are important factors boosting non-cash payments. In addition, the sales of desktop-PCs and the number of individuals who overed 35 years are the determinants of non-cash payments.